Composite amine mixed matrix membranes for high-pressure CO 2 -CH 4 separation: Synthesis, characterization and performance evaluation: Composite Amine Mixed Matrix Membranes - Fauzan, N.A.B. (Royal Society Publishing, 2020)
The key challenge in the synthesis of composite mixed matrix membrane (MMMs) is the incompatible membrane fabrication using porous support in the dry-wet phase inversion technique. The key objective of this research is to synthesize thin composite ternary (amine) mixed matrix membranes on microporous support by incorporating 10 wt of carbon molecular sieve (CMS) and 5-15 wt of diethanolamine (DEA) in polyethersulfone (PES) dope solution for the separation of carbon dioxide (CO 2) from methane (CH 4) at high-pressure applications. The developed membranes were evaluated for their morphological structure, thermal and mechanical stabilities, functional groups, as well as for CO 2 -CH 4 separation performance at high pressure (10-30 bar). The results showed that the developed membranes have asymmetric structure, and they are mechanically strong at 30 bar. This new class of PES/CMS/DEA composite MMMs exhibited improved gas permeance compared to pure PES composite polymeric membrane. CO 2 -CH 4 perm-selectivity enhanced from 8.15 to 16.04 at 15 wt of DEA at 30 bar pressure. The performance of amine composite MMMs is theoretically predicted using a modified Maxwell model. The predictions were in good agreement with experimental data after applying the optimized values with AARE = â¼less than 2 and R 2 = 0.99. Â© 2020 The Authors.